Rapid determination of erythrocyte sedimentation rate (ESR) by an electrically driven blood droplet biosensor - Kumar S.; Ram R.; Sarkar A.; Dasgupta S.; Chakraborty S. (My University, 2025)
In healthcare practice, the sedimentation rate of red blood cells (erythrocytes) is a widely used clinical parameter for screening of several ailments such as stroke, infectious diseases, and malignancy. In a traditional pathological setting, the total time taken for evaluating this parameter varies typically from 1 to 2 h. Furthermore, the volume of human blood to be drawn for each test, following a gold standard laboratory technique (alternatively known as the Westergren method), varies from 4 to 5 ml. Circumventing the above constraints, here we propose a rapid (∼1 min) and highly energy efficient method for the simultaneous determination of hematocrit and erythrocyte sedimentation rate (ESR) on a microfluidic chip, deploying electrically driven spreading of a tiny drop of blood sample (∼8 μl). Our unique approach estimates these parameters by correlating the same with the time taken by the droplet to spread over a given radius, reproducing the results from more elaborate laboratory settings to a satisfactory extent. Our novel methodology is equally applicable for determining higher ranges of ESR such as high concentration of bilirubin and samples corresponding to patients with anemia and patients with some severe inflammation. Furthermore, the minimal fabrication steps involved in the process, along with the rapidity and inexpensiveness of the test, render the suitability of the strategy in extreme point-of-care settings. © 2020 Author(s).